New Insights on Eggplant/Tomato/Pepper Synteny and Identification of Eggplant and Pepper Orthologous QTL - Rinaldi, Riccardo; Van Deynze, Allen; Portis, Ezio; Rotino, Giuseppe L.; Toppino, Laura; Hill, Theresa; Ashrafi, Hamid; Barchi, Lorenzo; Lanteri, Sergio (Frontiers in Plant Science, 2016)
Eggplant, pepper and tomato are the most exploited berry-producing vegetables within the Solanaceae family. Their genomes differ in size, but each has 12 chromosomes which have undergone rearrangements causing a redistribution of loci. The genome sequences of all three species are available but differ in coverage, assembly quality and percentage of anchorage. Determining their syntenic relationship and QTL orthology will contribute to exploit genomic resources and genetic data for key agronomic traits. The syntenic analysis between tomato and pepper based on the alignment of 34,727 tomato CDS to the pepper genome sequence, identified 19,734 unique hits. The resulting synteny map confirmed the 14 inversions and 10 translocations previously documented, but also highlighted 3 new translocations and 4 major new inversions. Furthermore, each of the 12 chromosomes exhibited a number of rearrangements involving small regions of 0.5-0.7 Mbp. Due to high fragmentation of the publicly available eggplant genome sequence, physical localization of most eggplant QTL was not possible, thus, we compared the organization of the eggplant genetic map with the genome sequence of both tomato and pepper. The eggplant/tomato syntenic map confirmed all the 10 translocations but only 9 of the 14 known inversions; on the other hand, a newly detected inversion was recognized while another one was not confirmed. The eggplant/pepper syntenic map confirmed 10 translocations and 8 inversions already detected and suggested a putative new translocation. In order to perform the assessment of eggplant and pepper QTL orthology, the eggplant and pepper sequence-based markers located in their respective genetic map were aligned onto the pepper genome. GBrowse in pepper was used as reference platform for QTL positioning. A set of 151 pepper QTL were located as well as 212 eggplant QTL, including 76 major QTL (PVE ≥ 10%) affecting key agronomic traits. Most were confirmed to cluster in orthologous chromosomal regions. Our results highlight that the availability of genome sequences for an increasing number of crop species and the development of “ultra-dense” physical maps provide new and key tools for detailed syntenic and orthology studies between related plant species.